Elastic-Plastic Fracture 1979
DOI: 10.1520/stp35830s
|View full text |Cite
|
Sign up to set email alerts
|

On Criteria for J-Dominance of Crack-Tip Fields In Large-Scale Yielding

Abstract: Very detailed finite-strain/finite-element analyses of deeply cracked plane-strain center-notch panel and single-edge crack bend specimens were generated using nonhardening and power-law-hardening constitutive laws. The deformation was followed from small-scale yielding into the fully plastic range. The objective was to provide insight as to the minimum specimen size limitations, relative to the characteristic crack-tip opening dimension J/σo, necessary to assure a J-based dominance of the crack-tip region. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Shear lips are regions where the crack tip constraint is low and so this suggests that although the crack tip constraint in the central region of the specimen is the same for different geometries, the average crack tip constraint is lower for geometries with lower plastic constraint factors. The greater difficulty in maintaining high constraint in geometries with low plastic constraint factors is consistent with the results from finite element studies [11].…”
Section: Ctod Isupporting
confidence: 80%
“…Shear lips are regions where the crack tip constraint is low and so this suggests that although the crack tip constraint in the central region of the specimen is the same for different geometries, the average crack tip constraint is lower for geometries with lower plastic constraint factors. The greater difficulty in maintaining high constraint in geometries with low plastic constraint factors is consistent with the results from finite element studies [11].…”
Section: Ctod Isupporting
confidence: 80%
“…It is well known from elasticplastic finite-element analyses (FEM) that the normal stress ahead of a sharp crack can, theoretically, reach values that are more than four times the yield strength. 36) It follows that tough steels with yield strength much above 2 GPa are liable to normal stresses of the order of 10 GPa.…”
Section: Tensile Strengthmentioning
confidence: 99%
“…The most thoroughly researched is 5.5Ni steel (typical composition: Fe-5.9Ni-1.2Mn-0.7Cr-0.2Mo-0.06C), which can serve as an example. 36) The intent of the QLT treatment is to achieve a dense distribution of stable austenite precipitates like that in 9Ni steel with lower Ni content. If a 6Ni steel is tempered like 9Ni steel very little austenite is formed, and that which does appear is thermally unstable.…”
Section: The Qlt Treatmentmentioning
confidence: 99%
“…Moran et al [21] have demonstrated that as in other geometries [22], the size of the finite strain zone in a circumferentially cracked bar is equal to about two ~CTOD. In the present case, the values of ~c are very large (even though they decrease with decreasing ligament diameters) and the small strain zone does not cover the major part of the ligament area as it usually does.…”
Section: Cracking Initiation Criterionmentioning
confidence: 88%